IN SILICO CHARACTERIZATION OF IMEGLIMIN’S INTERACTION WITH INFLAMMATORY AND MITOCHONDRIAL TARGETS USING MOLECULAR DOCKING AND MOLECULAR DYNAMICS - YAZHINI P M; RAMYA S; PARVATHAREDDY SOWMYA; KAVITHA RAMASAMY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of the study is to elucidate the molecular basis of Imeglimin’s mitochondrial protective and anti-inflammatory effects through in silico analysis of its interactions with key mitochondrial and inflammatory regulatory proteins. Methods: Molecular docking and 100 ns molecular dynamics simulations were performed to assess Imeglimin’s binding to five key targets: AKT1, Parkin, DRP1, NLRP3, and hexokinase 2. Analyses included root mean square deviation, root mean square fluctuation, radius of gyration, principal component analysis, dynamic cross-correlation matrices, and MM/GBSA-based binding-free energy calculations. Results: Imeglimin exhibited stable interactions with critical regulatory residues in AKT1 (kinase domain), Parkin (Ubl and RING regions), DRP1 (GTPase domain), and NLRP3 (NATCH and LRR domains). These interactions were associated with constrained conformational mobility and stabilization of inactive-like states. Hexokinase 2 showed lower binding affinity and higher flexibility. MM/GBSA analysis indicated favorable binding energetics. Conclusion: Imeglimin acts as a multi-target modulator of mitochondrial proteins, stabilizing functionally inactive or constrained conformations without inducing structural destabilization. These findings provide a structural framework for its reported mitochondrial protective and anti-inflammatory function.